Constructing a New Blended Learning Technique: Using English Discovery as Learning Management System for Test Format Familiarity - Agil Abdur Rohim; Oikurema Purwati; Syafiul Anam; Ahmad Munir (ELITE JOURNAL, 2023)
ABSTRACTBlended learning offers numerous benefits to language learning and teaching. The benefits attract higher education institutions to implement the blended learning for advancing students’ learning outcome. The need to boost students’ learning outcome occurs simultaneously with the demand for higher education institutions to measure students’ English proficiency. Consequently, certain English proficiency test is required for students’ admission and students’ graduation. Thus, this paper aimed to offer new blended learning technique to boost students’ learning outcome and simultaneously to prepare students taking certain English proficiency tests. English Discoveries (ED) from Edusoft, as a tertiary from Educational Testing Service (ETS) was selected as learning management system (LMS) due to its vast topics and language skills coverage. Comprehensive materials and diverse practices from ED were used to be the resources for test formats familiarity. This study has shown that ED materials and practices were similar with TOEIC Listening and Reading sections and TOEFL ITP Listening, Structure and Written Expression, and Reading section. By learning in blended environment with ED, students were predicted to be more familiar with TOEIC and TOEFL ITP test formats. Being familiarized with the test formats should increase the possibility for students to have higher English proficiency score. Keywords: blended learning; test format familiarity